Plant-to-planet analysis of CO2-based methanol processes. Issue 12 (22nd October 2019) - González-Garay, Andrés; Frei, Matthias S.; Al-Qahtani, Amjad; Mondelli, Cecilia; Guillén-Gosálbez, Gonzalo; Pérez-Ramírez, Javier
Abstract : The unprecedented application of planetary boundaries in chemical process assessment uncovers the otherwise unidentifiable potential of green methanol in establishing a sustainable industry. Abstract : A critical assessment of methanol production from carbon dioxide and renewable hydrogen is here presented, gathering an insightful picture of its wide sustainability and establishing a hierarchy of factors dictating its performance. Process simulation and life-cycle analysis indicate that green methanol is at present economically unattractive, i.e., it has a 1.3–2.6-fold higher cost compared to the current fossil-based analogue, even when considering indirect environmental costs via monetisation of impacts and a potential CO2 tax of at least 430.5 USD tCO2 -eq −1 . This is mainly due to the high price of hydrogen (water electrolysis powered with solar, wind, and nuclear energy, or biomass gasification, up to 73% of the total cost), which shall drop significantly due to reductions in electricity costs and technological advances. The scenario radically changes when quantifying for the first time the absolute sustainability of this carbon capture and utilisation route through eight planetary boundaries, revealing that CO2 -based methanol would contribute to operating safely within critical ecological limits of the Earth linked to carbon emissions, currently transgressed by the conventional process. Our plant-to-planet assessment embraces the full potential role of emerging processes in sustainable development, which should prevail over purely economic arguments, subject to market fluctuations and technological advances.